Indication of a p–ϕ bound state from a correlation function analysis - Chizzali, Emma; Kamiya, Yuki; Del Grande, Raffaele; Doi, Takumi; Fabbietti, Laura; Hatsuda, Tetsuo; Lyu, Yan (Physics letters. B, 2024)
The existence of a nucleon–ϕ (N–ϕ) bound state has been subject of theoretical and experimental investigations for decades. In this letter, indication of a p–ϕ bound state is found, using for the first time two-particle correlation functions as alternative to invariant mass spectra. Newly available lattice calculations for the spin 3/2 N–ϕ interaction by the HAL QCD collaboration are used to constrain the spin 1/2 counterpart from the fit of the experimental p–ϕ correlation function measured by ALICE. The corresponding scattering length and effective range are f0(1/2)=(−1.54−0.53+0.53(stat.)−0.09+0.16(syst.)+i⋅0.00−0.00+0.35(stat.)−0.00+0.16(syst.)) fm and d0(1/2)=(0.39−0.09+0.09(stat.)−0.03+0.02(syst.)+i⋅0.00−0.04+0.00(stat.)−0.02+0.00(syst.)) fm, respectively. The results imply the appearance of a p–ϕ bound state with an estimated binding energy in the range of 12.8−56.1 MeV.